Development of Learning Animation Videos Using the Sparkol Videoscribe Application to Improve Students' Understanding of Mathematical Concepts at SMPS Sultan Iskandar Muda - Edwin Gabril Sitepu; Tiur Malasari Siregar (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to obtain learning animation videos using the Sparkol videoscribe application which are valid, practical, effective, and can improve students' understanding of mathematical concepts. The trials carried out were individual, small group and field trials. The results of the study show that: (1) Video learning meets valid criteria with a percentage of 95% for media and 97% for material, (2) Video learning meets practicality criteria with a percentage of 87% for teacher responses and 90% for student responses, ( 3) The learning videos have fulfilled the effective criteria where: a) the learning completeness is 86%; b) more than 65% of students achieve 75% of the learning objectives for each indicator; c) Student response with a positive percentage of 87%. the ability to understand students' mathematical concepts on the gain test increased by 0.77.